Geographic Diversification of the Supply Chains of Japanese Firms. (8th February 2021) - Todo, Yasuyuki; Inoue, Hiroyasu
Abstract : Diversifying supply chains has been a policy objective of the Japanese government to construct a robust and resilient economy since the spread of COVID‐19 in the final stages of the Abe Administration. Although geographically expanded supply chains incur a risk of inflows of negative economic shocks from other regions and countries, this risk can be alleviated by more diversification. In addition, diversified supply chains are found to promote the performance of firms. Recently, the domestic supply chains of Japanese firms started to be diversified, but firms still agglomerate in Tokyo substantially. Moreover, the international supply chains of Japanese firms rely considerably on Chinese suppliers and clients. Therefore, more geographic diversification of supply chains of Japanese firms is suggested for the more robust, resilient, and high‐growth economy in the post Abenomics period, including diversifying within Japan, reducing the reliance on China, and strengthening links with developed countries, with the help of the government.